ANALISIS OPTIMALISASI PRODUKSI PADA USAHA AGRIBISNIS PUPUK PHOSKA PHOSKA DI CV. DEWI SRI RAMA KEPULUNGAN, KECAMATAN GEMPOL, KOTA PASURUAN, JAWA TIMUR - administrator, administrator; Sabdu, Safrianus; Susanto, Heri (Fakultas Pertanian Universitas Wijaya Putra, 2023)
Fertilizer is wrong one production factors main besides, land, power work andcapital. Fertilization hold important role in effort increase agricultural product. Fertilizeris which materials added on growing media plant or plant For sufficient needs the requirednutrients plants to be productive with good. Pasuruan as Wrong one regency big East JavaProvince after city surabaya. Fertilizer is element hara which edded in land for increasefertility land and plant. Study this aim know is business production Fertilizer npk phoskain Cv. Dewi Sri Rama, Kepulungan, Subdistrict Gempol, Regency Pasuruan, East Java hasrun in a manner efficient and get profit which optimal or no. Method study which used isdescription analysis data which used thatis (1).appropriateness business (2).profit businesswhich obtained difference from reception cost total. Results study showing that evaragebusiness production Fertilizer npk phoska in Cv. Dewi Sri Ram, kepulungan, SubdistrictGempol, Regency Pasuruan, East Java as big Rp. 275.364.444,–, evarage income whichobtained is Rp. 300.000.000,-, so that profit evarage is Rp. 24.635.556,- value k BEP 1.974and value efficiency R/C ratio more from one is Rp. 1.333, it means every Rp.50.000 whichissued producer will obtain income as big Rp.67,25